World Film Locations : Dublin. - Conolly, Jez; Whelan, Caroline (Intellect Books, 2011)
World Film Locations: Dublin aims to present a selective snapshot of the city through the medium of the movies made or set in it and allow the reader to inhabit these spaces, passing through a stimulating choice of words and pictures that inform and precipitate an imagined exploration. It is a collection of over forty reviews of scenes from films, either shot or set in Dublin, illustrated by images from the scenes in question, and photographs of locations, often as they are today. Together, the words and images expose the relationship between a scene's setting and its impact on the viewer. The short scene reviews are interspersed with more detailed, meditative essays that are designed to examine in greater depth some of the key aspects of Dublin as seen onscreen; the city's political and literary histories are appraised, as are its music scene, its familiar faces, its element of organised crime and its fluctuating attributes before, during and after the Celtic Tiger era. Taken as a whole, this book constitutes a rare written instance of Dublin encapsulated in moments of film, brought together and supplemented by a pictorial toolkit designed to enable a conceptual tour of the city in its various incarnations.